In vitro metabolism of an estrogen‐related receptor γ modulator, GSK5182, by human liver microsomes and recombinant cytochrome P450s. (24th January 2015) - Joo, Jeongmin; Wu, Zhexue; Lee, Boram; Shon, Jong Cheol; Lee, Taeho; Lee, In‐Kyu; Sim, Taebo; Kim, Kyung‐Hee; Kim, Nam Doo; Kim, Seong Heon; Liu, Kwang‐Hyeon
Abstract GSK5182 (4‐[(Z)‐1‐[4‐(2‐dimethylaminoethyloxy)phenyl]‐hydroxy‐2‐phenylpent‐1‐enyl]phenol) is a specific inverse agonist for estrogen‐related receptor γ, a member of the orphan nuclear receptor family that has important functions in development and homeostasis. This study was performed to elucidate the metabolites of GSK5182 and to characterize the enzymes involved in its metabolism. Incubation of human liver microsomes with GSK5182 in the presence of NADPH resulted in the formation of three metabolites, M1, M2 and M3. M1 and M3 were identified as N‐desmethyl‐GSK5182 and GSK5182 N‐oxide, respectively, on the basis of liquid chromatography‐tandem mass spectrometric (LC‐MS/MS) analysis. M2 was suggested to be hydroxy‐GSK5182 through interpretation of its MS/MS fragmentation pattern. In addition, the specific cytochrome P450 (P450) and flavin‐containing monooxygenase (FMO) isoforms responsible for GSK5182 oxidation to the three metabolites were identified using a combination of correlation analysis, chemical inhibition in human liver microsomes and metabolism by expressed recombinant P450 and FMO isoforms. GSK5182 N‐demethylation and hydroxylation is mainly mediated by CYP3A4, whereas FMO1 and FMO3 contribute to the formation of GSK5182 N‐oxide from GSK5182. The present data will be useful for understanding the pharmacokinetics and drug interactions of GSK5182 in vivo. Copyright © 2014 John Wiley & Sons, Ltd.